Microdialysis and proteomics of subcutaneous interstitial fluid reveals increased galectin-1 in type 2 diabetes patients - Fryk, Emanuel; Schmelz, Martin (Metabolism, 2016)
Objective - To identify a potential therapeutic target for type 2 diabetes by comparing the subcutaneous interstitial fluid from type 2 diabetes patients and healthy men. - Methods - Proteomics was performed on the interstitial fluid of subcutaneous adipose tissue obtained by microdialysis from 7 type 2 diabetes patients and 8 healthy participants. 851 proteins were detected, of which 36 (including galectin-1) showed significantly altered expression in type 2 diabetes. We also measured galectin-1 expression in: (1) adipocytes isolated from adipose tissue biopsies from these participants; (2) subcutaneous adipose tissue of 24 obese participants before, during and after 16weeks on a very low calorie diet (VLCD); and (3) adipocytes isolated from 6 healthy young participants after 4weeks on a diet and lifestyle intervention to promote weight gain. We also determined the effect of galectin-1 on glucose uptake in human adipose tissue. - Results - Galectin-1 protein levels were elevated in subcutaneous dialysates from type 2 diabetes compared with healthy controls (p<0.05). In agreement, galectin-1 mRNA expression was increased in adipocytes from the type 2 diabetes patients (p<0.05). Furthermore, galectin-1 mRNA expression was decreased in adipose tissue after VLCD (p<0.05) and increased by overfeeding (p<0.05). Co-incubation of isolated human adipocytes with galectin-1 reduced glucose uptake (p<0.05) but this was independent of the insulin signal. - Conclusion - Proteomics of the interstitial fluid in subcutaneous adipose tissue in vivo identified a novel adipokine, galectin-1, with a potential role in the pathophysiology of type 2 diabetes.